Preaching: Truth sharing as a prophetic voice - M. Nel (Acta Theologica)
What kind of preaching and what kind of preacher will facilitate the cultivation of contextually relevant missional congregations? A main thesis in this search was and still is that integrating and coordinating all ministries are necessary to develop such missional congregations. But what role does preaching play as part of this whole? In this regard, interviews were held with 24 pastors and academics in the United States of America. In this and another teamresearch project, it was discovered how challenging it is to help congregations transform into intercultural sensitivity and cultivate a new missional culture. In this article, I intentionally explore the work done by Patrick Johnson. He explored the work of three homileticians and eventually brought them in conversation with the ecclesiology of Karl Barth – in developing a “missional homiletics of witness” (Johnson 2015:139) – which I observe to include prophetic preaching that will challenge communities of faith towards missional faithfulness and transformation.